Exploration of consumers' navigation of online health information - Lee, Kenneth Junjie (Curtin University, 2015)
This research investigated how consumers with chronic health conditions seek online health information to assist self-management of their conditions. The proportion of online information seekers requiring support to find pertinent health information was determined, and their preferences for support were explored. A commercial initiative in this field was presented and critiqued as a case study. An exploratory sequential mixed methodological design overarched the research, and theories and models relating to this research were inductively critiqued.